Parasitic infections and their tissue response: a histopathological study - Manoharan, A.; Srinivasan, Sowmya (International Journal of Research in Medical Sciences, 2017)
Background: Many pathogenic organisms including parasites cause inflammatory lesions and microscopic findings are useful tool for the aetiological diagnosis. The causes of parasite induced tissue damage can either be due to the physical pressure exerted by the parasites or the toxic secretory products which may lead to hypersensitivity reactions. The commonly encountered tissue responses are eosinophilic infiltration, abscess formation and granulomatous inflammation. Main objective of the study is to study the parasitic infections involving various tissues and organs and to assess the tissue response elicited against these parasites. Methods: The histopathologically diagnosed parasitic infections over a period of 7 years from January 2007 to December 2013 were analysed. The histological identification of parasite and tissue reaction was evaluated in correlation with clinical presentation. Enterobius vermicularis which is the most common parasitic infestation in appendix was excluded from the study. Results: Over a period of 7 years 9 cases of parasitic infections were found. These include 2 cases each of filariasis, cysticercosis, and hydatid cyst, and 1 case each of ascaris enteritis, amoebic colitis, and conjunctival parasite. The specific tissue reactions included eosinophilic infiltrate in filariasis and ascaris enteritis and xanthogranulomatous reaction in cysticercosis. Conclusions: Among the 9 cases only 2 hydatid cysts and one genital filariasis were clinically diagnosed. Remaining cases were incidentally found only on the histopathological examination. This emphasises that careful histopathological examination is essential for the diagnosis of these lesions to provide specific treatment for the patients.